Timber Potential of a Secondary Forest with Araucaria in Brazilian Atlantic Forest: Implications for Small-Scale Management - Leandro Correa Pinho; Daisy Christiane Zambiazi; Mário Dobner; Alexander Christian Vibrans; Alexandre Siminski; Vinicius Costa Cysneiros (Small-scale Forestry, 2026)
Despite a three-decade-long prohibition on the harvesting of Araucaria angustifolia and other timber species in the Atlantic Forest, the conservation status remains critical, as evidenced by the ongoing illegal exploitation, deforestation, and habitat fragmentation. This underscores the need to develop and implement effective strategies to reconcile the use of forest resources with the maintenance of their ecosystems and associated ecosystem services. This study assessed the timber potential of a secondary forest fragment with Araucaria by characterizing the composition, forest structure and timber stocks, while accounting for timber and stem quality. Fifty tree species were sampled, 72% of which have some timber use and 19% of which have high quality timber. The average timber stock was 177.6 m 3 ha −1 , with Araucaria angustifolia standing out, accounting for 28 m 3 ha −1 , mainly in high-quality commercial stems. Two forest types were identified within the studied area: a diversified forest and a high stock forest, representing two groups of sampling units with marked differences in timber quality and stocks. The highest quality stock was concentrated in the commercial ( dbh > 50 cm) and pre-commercial (30 ≤ dbh ≤ 50 cm) classes. A. angustifolia and Nectandra megapotamica stood out for providing high-quality timber and for being dominant commercial species. The results revealed the need for differentiated management practices between forest types. These practices should prioritize the sustainable use of dominant commercial species and the use of lower-quality stems for secondary products. The results indicate that small-scale management, associated with silvicultural treatments, could contribute to integrating conservation and income generation in secondary forests, promoting the maintenance of ecosystem services.

Recovery of secondary forest following selective timber harvest in the Brazilian Atlantic Forest - Daisy Christiane Zambiazi; Alfredo Celso Fantini; Daniel Piotto; Alexandre Siminski; Alexander Christian Vibrans; Ilyas Siddique; Geferson Elias Piazza; Marielos Peña-Claros (Forest Ecology and Management, 2026)

A Diachronic Analysis of the Relationships Between Humans and Araucaria Forests - Ana H. Ladio; Alexandre Siminski; Karine L. dos Santos; Mauricio Sedrez dos Reis (Ethnobotany and Economic Botany, 2026)

Present and future distribution of endangered and economically important Ocotea species in the Brazilian Atlantic Forest: Implications for conservation and restoration - Gabriela dos Santos Alves; Alexandre Siminski; Amanda Köche Marcon; Cesar Augusto Marchioro (Forest Ecology and Management, 2024)

Biotic interactions under risk: climate change drives spatial mismatch between a critically endangered tree and its seed dispersers and predators - Cesar Augusto Marchioro; Flavia da Silva Krechemer; Karine Louise dos Santos; Alexandre Siminski (Climatic Change, 2023)

Prioritization of key indicators for the classification of successional stages in regenerating subtropical Atlantic forest, Southern Brazil: a proposal based on multivariate order statistics - Adriano Bressane; Alexandre Siminski; Isadora Gurjon Gomes; Carrie Peres Melo; Graziele Coraline Scofano da Rosa; Amanda Louisi dos Santos Galvão; Mirela Beatriz Silva; Líliam César de Castro Medeiros; Rogério Galante Negri (Environment Systems and Decisions, 2023)

Computer-aided classification of successional stage in subtropical Atlantic Forest: a proposal based on fuzzy artificial intelligence - Adriano Bressane; Isadora Gurjon Gomes; Graziele Coraline Scofano da Rosa; Caio Cesar Moraes Brandelik; Mirela Beatriz Silva; Alexandre Siminski; Rogério Galante Negri (Environmental Monitoring and Assessment, 2023)

Arbuscular mycorrhizal fungal community assembly in agroforestry systems from the Southern Brazil - Lídia Klestadt Laurindo; Tancredo Augusto Feitosa de Souza; Lucas Jónatan Rodrigues da Silva; Thays Bragagnolo Casal; Karoline de Jesus Conceição Pires; Sarah Kormann; Djalma Eugênio Schmitt; Alexandre Siminski (Biologia, 2021)